Investigation of RBFNN Based on Improved PSO Optimization Algorithm for Performance and Emissions Prediction of a High‐Pressure Common‐Rail Diesel Engine. Issue 3 (4th January 2023) - Wang, Yuhua; Wang, Guiyong; Yao, Guozhong; Yang, Lu; Li, Jinlong; He, Shuchao
Abstract: The purpose of this study is improve calibration efficiency and obtain accurate diesel engine operating parameters, achieving improved diesel engine emissions and fuel efficiency. A PSO‐RBF (particle swarm optimization‐radial basis function) diesel engine performance prediction model combining an improved PSO (particle swarm optimization algorithm and an RBF neural network is proposed. A space‐filling experimental design method for diesel engine performance prediction is proposed based on the actual operating conditions of diesel engines. Training data are collected at the bench to build the RBF prediction model. An optimization PSO search method is proposed to improve the PSO optimization capability. An improved PSO algorithm is used to optimize the model and improve prediction accuracy. Then the BSFC (diesel brake‐specific fuel consumption), NO x ((Nitrogen Oxid), CO (Carbon Monoxide), and HC (Hydrocarbon) prediction models are constructed. Results show that the PSO‐RBF can find the global solution with good prediction accuracy and generalization ability during small amounts of data. The PSO‐RBF model fitting degrees of BSFC, NO x, CO, and HC are 0.9952, 0.9910, 0.9820, and 0.9870 respectively. Mean relative errors are 3.02%, 2.78%, 1.39%, and 2.01% respectively. Mean absolute percentage errors are 1.58%, 3.26%, 3.69%, and 2.96% respectively. The optimized model R 2 (Model determination coefficient) is improved by 0.065, 0.102, 0.10, and 0.085, respectively. Abstract : In the proposed PSO‐RBF (particle swarm optimization‐radial basis function) diesel engine performance prediction model, compared to the model before optimization, the model determination coefficients of BSFC, NO x, CO, and HC are increased by 0.065, 0.102, 0.10, and 0.085, respectively. In addition, a test design method for diesel engines is presented. The PSO search method has also been improved.